Zinc impregnated cellulose nanocomposites: Synthesis, characterization and applications. (November 2016) - Ali, Attarad; Ambreen, Sidra; Maqbool, Qaisar; Naz, Sania; Shams, Muhammad Fahad; Ahmad, Madiha; Phull, Abdul Rehman; Zia, Muhammad
Abstract: Nanocomposite materials have broad applicability due to synergistic effect of combined components. In present investigation, cellulose isolated from citrus peel waste is used as a supporting material; impregnation of zinc oxide nanoparticles via co-precipitation method. The characterization of nano composite is carried out through Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD) analysis, scanning electron microscopy (SEM) and Thermo-gravimetric analysis (TGA) resulting less than 10 µm cellulose fiber and approx. 50 nm ZnO NPs. Zinc oxide impregnated cellulose (ZnO–Cel) exhibited significant bacterial devastation property when compared to ZnO NPs or Cellulose via disc diffusion and colony forming unit methods. In addition, the ZnO–Cel exhibited significant total antioxidant, and minor DPPH free radical scavenging and total reducing power activities. The nano composite also showed time dependent increase in photocatalytic by effectively degrading methylene blue dye up to 69.5% under sunlight irradiation within 90 min. The results suggest effective utilization of cellulose obtained from citrus waste and synthesis of pharmacologically important nano-composites that can be exploited in wound dressing; defence against microbial attack and healing due to antioxidative property, furthermore can also be used for waste water treatment. Highlights: The method is simple for the synthesis of the various metal-polymer composites. The XRD pattern confirmed the crystalline nature of ZnO–Cel. FTIR, SEM and TGA pattern revealed the Zn impregnation in cellulose and nano composites synthesis. The ZnO–Cel exhibited antibacterial activity against E. coli and S. aureus and significant total antioxidant activity. The ZnO–Cel also showed considerable photocatalytic activity.